Paediatric dentistry experience of the first cohort of students to graduate from Dublin Dental School and Hospital under the new curriculum - D. FINUCANE, J. H. NUNN & A. C. O’CONNELL (Paediatric Dentistry, 2004)
To assess undergraduate clinical experience in Paediatric Dentistry in students graduating under a new curriculum.